Optimalisasi Kandungan Gizi dan Aktivitas Antioksidan Bubur Instan berbasis Beras Pratanak dan Tepung Mocaf yang Difortifikasi Bayam Merah: Optimization of Nutritional Content and Antioxidant Activity of Instant Porridge based on Parboiled Rice and Mocaf Flour Fortified with Red Spinach - Hanifa, Zulfa Nur; Emilia, Esi (Amerta Nutrition, 2024)
Background: Instant porridge is a type of processed food that does not require cooking in its preparation.  The use parboiled rice, mocaf flour, and red spinach in instant porridge production offers a viable alternative for developing nutrient-dense and antioxidant-rich processed foods. Parboiled rice, a modified rice variant, is selected for its low glycemic index and high nutritional value. Mocaf flour, a gluten-free alternative, is used to enhance the product's nutritional profile, while red spinach is added to boost the antioxidant content of the instant porridge. Objectives: This study aims to investigate the proximate composition and evaluate the antioxidant activity of instant porridge. Methods: The instant porridge was formulated with a composition of 70% parboiled rice, 30% mocaf flour, and 2% red spinach. Proximate analysis was performed to determine the moisture, ash, protein, fat, and carbohydrate content, following the methods outlined in the AOAC 1995 guidelines. Antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay to assess the porridge's free radical scavenging capacity. Results: The instant porridge produced was found to have a high nutritional content. The antioxidant activity was evaluated based on the IC50 value, the instant porridge demonstrated a notable IC50 value of 73.28 μg/ml, indicating that it possesses strong antioxidant properties / indicating that it is categorized as a strong antioxidant. The nutritional and antioxidant properties of the instant porridge can be attributed to the main ingredients used in its production. Conclusions: The instant porridge produced provided high nutritional content and antioxidant activity, making it a good choice for meeting daily nutritional needs.